1979
DOI: 10.1111/j.1528-1157.1979.tb04771.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drugs and Vitamin D Supplementation

Abstract: The incidence of biochemical signs of vitamin D deficiency and the effects of vitamin D supplementation were investigated in 83 children and 95 adults on chronic antiepileptic therapy and 40 mentally retarded controls living under comparable conditions. Low 25-hydroxyvitamin D and serum calcium, and elevated immunoreactive parathyroid hormone and alkaline phosphatase was a common finding in all groups, but in patients on antiepileptic drugs, signs of vitamin D deficiency were recorded more frequently. Suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
3

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 37 publications
3
40
0
3
Order By: Relevance
“…In accordance with other reports on calcium-phosphate metabolism in anticonvulsant treated patients (Bonfils et al, 1976;Christiansen et al, 1974;Hahn, 1976;Offermann et al, 1979) our patients demonstrated significant elevations of serum alkaline phosphatase and iPTH, hypocalciuria, hypomagnesemia and a reduced calcium-phosphate product in serum.…”
Section: Discussionsupporting
confidence: 95%
“…In accordance with other reports on calcium-phosphate metabolism in anticonvulsant treated patients (Bonfils et al, 1976;Christiansen et al, 1974;Hahn, 1976;Offermann et al, 1979) our patients demonstrated significant elevations of serum alkaline phosphatase and iPTH, hypocalciuria, hypomagnesemia and a reduced calcium-phosphate product in serum.…”
Section: Discussionsupporting
confidence: 95%
“…Effects of epilepsy treatment on vitamin D status in children More than three decades ago, Offerman et al [52] first reported the high prevalence of low vitamin D status among children with epilepsy. Since then, extensive research on vitamin D deficiency associated with anticonvulsant drugs in pediatric patients has been conducted [53][54][55][56][57][58][59][60].…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…2 AED medication, particularly long-term therapy or polytherapy, is recognized to be associated with hypovitaminosis D. [3][4][5] Adults with epilepsy are known to be at considerably increased risk for bone fractures compared with the general population, and increasing age and duration of AED treatment are significant risk factors. [6][7][8] In 1979, Offerman et al 9 documented that 72% of 83 children aged 10 to 16 years with epilepsy and 50% of 16 control patients exhibited 25-hydroxy vitamin D (25OHD) <15 ng/mL. Since then, several cross-sectional studies evaluated the prevalence of hypovitaminosis D in pediatric epilepsy.…”
Section: Introductionmentioning
confidence: 98%